2005
DOI: 10.4161/cc.4.8.1928
|View full text |Cite
|
Sign up to set email alerts
|

Histone Acetylation, Chromatin Remodelling and Nucleotide Excision Repair: Hint from the Study on MFA2 in Saccharomyces cerevisiae

Abstract: Nucleotide excision repair (NER) is a sophisticated repair pathway that the cell utilizes to remove a broad range of DNA damage to help maintain the functional integrity of the genome. In the context of DNA packaged into chromosomes it is clear that the NER machinery does not repair all regions with equal efficiency. Recently, we found after UV that histone acetylation and chromatin remodelling were activated. UV irradiation triggers genome-wide histone hyperacetylation at both histone H3 and H4. However, in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…It is not clear why the JNK pathway failed to compensate for LPS-induced IL-12p40 production in the presence of inhibitors specific for the calcium pathway. In addition to signal transduction pathways, molecular mechanisms controlling gene expression involve chromatin remodeling and DNA methylation (67)(68)(69). Understanding the status of promoter methylation and chromatin remodeling may elucidate the mechanisms underlying the involvement of distinct signaling pathways controlling IL-12p40 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear why the JNK pathway failed to compensate for LPS-induced IL-12p40 production in the presence of inhibitors specific for the calcium pathway. In addition to signal transduction pathways, molecular mechanisms controlling gene expression involve chromatin remodeling and DNA methylation (67)(68)(69). Understanding the status of promoter methylation and chromatin remodeling may elucidate the mechanisms underlying the involvement of distinct signaling pathways controlling IL-12p40 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The observations that nef inhibited IL-12p40 transcription in the presence of functional AP-1 suggests that AP-1 in the presence of dysfunctional NFB may not be able to drive LPS-induced IL-12p40 transcription further suggesting a potential cooperation between the two factors. Besides signal transduction pathways, molecular mechanisms controlling gene expression involve chromatin remodeling and DNA methylation (63). In addition to the inhibition of JNK and NFB, intracellular nef may inhibit IL-12p40 transcription by altering the status of promoter methylation, and chromatin remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, direct evidence of roles for histone modifications and chromatin remodelling in NER has started to emerge. We previously showed that histone H3 acetylation by Gcn5 is activated in the repressed MFA2 promoter after UV irradiation in S. cerevisiae (40,41). This UV-induced histone H3 hyperacetylation is necessary for the efficient repair of UV-induced CPDs in this locus.…”
Section: Introductionmentioning
confidence: 99%